Uso das tecnologias internet para inovação: estudo em empresas brasileiras - Grützmann, André (2014)
This study investigated from quantitative and qualitative approaches the use of internet technologies to support innovation in Brazilian companies to propose a framework for web-based innovation. A scoping review of the literature showed the main uses of these technologies for every stage of innovation. A sample of 308 companies helped to characterize the uses of internet technologies on innovation. Factorial analysis identified two factors: 1) focus on innovation (idea competition, co-creation platforms, web mining, virtual worlds and other internet technologies); and 2) focus on communication and interaction (blogs, social networks, discussion forums, wikis). Also the study pointed out a factor called basic support (website, email, search engines). The qualitative approach showed that innovative interviewed companies used mainly social networks to support their innovation activities, but some reported investments in co-creation platforms. The web-based innovation framework proposes interrelationships between stages of the innovation process and internet technologies, in an integrated approach, also subsidizes for decision making in the adoption of Internet technologies in the context of innovation.